Dukungan Terhadap Pengembangan Hijauan Indigofera di Kabupaten Manggarai Barat: Tinjauan Faktor-Faktor yang Memengaruhi Adopsi - JERMIAS, JOHANIS A; Penu, Cardial Leverson Leo; Bulu, Petrus Malo; Koten, Bernadete; Moata, Melinda; Illi, Mardianus; Wera, Ewaldus (Jurnal Veteriner; Vol 22 No 1 (2021), 2021)
Ruminant productivity is influenced by the quality and quantity of forage. Forage plant that is prospectively developed is Indigofera which has advantages such as high nutrient content, low crude fiber, being able to live in dry areas, and low anti-nutrient. However, as an innovation, adoption, cultivation, and utilization in a sustainable manner depend on several factors. This study was aimed to investigate the potential adoption of Indigofera forage in West Manggarai Regency with a focus on the factors that influence adoption. Data were collected through observations, individual interviews, Focus Group Discussions and study of documents. The number of respondent’s farmers was 59 from seven villages in five sub-districts. The results showed that in terms of the respondent’s characteristic factors, 96.61% were in the productive age, 94.7% had a formal education background, a sufficient number of a household member and a good perception of the Indigofera. From the socioeconomic condition factor, there are introductions of innovations through different patterns involving different actors with different results which can be used as an introduction model. From the characteristic factor, Indigofera forage has higher nutritional content compared to other popular forages, easy to live in the dry land, the process of breeding and cultivation is not difficult for the profession of farmers and has proven the results of development in other regions in Indonesia. Based on the facts and analysis, it was concluded that the Indigofera plant has the potential to be widely adopted and used by farmers in the West Manggarai Regency.